MONITORING AKTIVITAS DI JEJARING SOSIAL MENGGUNAKAN ALGORITMA SELECTION SORT PADA MEDIA SOSIAL PENDIDIKAN - Humaerah, Mutiah; Honggowibowo, Anton Setiawan; Nugraheny, Dwi (Compiler, 2016)
Monitoring the activity on social network is a web-based application used to monitor the activity o f students or children in socially mediated by parents or teachers. Social media educational been created to support student learning in school. The application o f monitoring usedSelection Sort Algorithm. Selection sort algorithm used to sort the data based on the results o f monitoring input the desired date. From the test results can be concluded that this application can be used to monitor the activity o f children in social media education based on status, comments,and messages. The results o f this study indicate that parents o f Mutiah (user) monitoring the activities o f their children based on the status o f the results o f an update 8 (eight) status starting from the date o f July 26, 2016 until August 2, 2016 with the sequences data from the newest date and time until the oldest data or sorting from the greatest data and average results obtained from testing using a questionnaire with 30 respondents and the amount calculated by the Likert method is 80.97% with the criteria o f "Very Good".